Macro Mineral Profile of Several Species of Brown Macroalgae from Lemukutan Waters as Biostimulant Candidates - Warsidah; Aritonang, Anthoni Batahan; Apindiati, Rita Kurnia (Jurnal Ilmiah Platax, 2024)
Biostimulants are natural or synthetic substances that can be used to stimulate plant growth, development, and defense responses and can be obtained from various sources such as plants, phytohormones, and microorganisms. Macroalgae is one of the potential marine biota that can be used as a biostimulant because it contains a lot of chemicals such as micro, macro minerals, and phytohormones. As a first step in exploring macroalgae from the waters of Lemukutan Island as biostimulant candidates, this research was carried out to determine the macro mineral content of calcium, potassium, sodium, and phosphorus from macroalgae types Turbinaria and Sargassum. The research was carried out using the atomic absorption spectrophotometric (AAS) analysis method. The results of determining the macro mineral content show that Turbinaria sp has a Calcium (Ca) content of 13.20 mg/kg, Potassium (K) of 31.24 mg/kg, Sodium (Na) of 21,45 mg/kg and Magnesium (Mg) of 17.5 mg/kg, while Sargassum sp has a Calcium (Ca) content of 10.50 mg/kg, Potassium (K) of 26.35 mg/kg, Sodium (Na) of 30.55 mg/kg and Magnesium (Mg) of 18.7 mg/kg. Keywords: Biostimulants, AAS, macro minerals, phytohormones. Abstrak Biostimulan adalah substansi alami atau sintetis yang dapat digunakan untuk merangsang pertumbuhan, perkembangan, dan respons pertahanan tanaman dan dapat diperoleh dari berbagai sumber seperti tanaman, fitohormon dan mikroorganisme. Makroalga adalah salah satu biota potensial dari laut yang dapat digunakan sebagai biostimulan karena kandungan kimianya sangat banyak seperti mineral mikro, makro dan fitohormon. Sebagai langkah awal dalam eksplorasi makroalga dari perairan pulau Lemukutan  sebagai kandidat biostimulan, maka penelitian ini dilakukan untuk menentukan kandungan makro mineral kalsium, kalium, natrium dan posfor dari makroalga jenis  Turbinaria dan Sargassum. Penelitian dilakukan menggunakan metode analisis spektrofotometri serapan atom (SSA). Hasil penentuan kandungan mineral makro tersebut menunjukkan Turbinaria sp memiliki kandungan  Kalsium (Ca) sebesar 13,20 mg/kg, Kalium (K)  sebesar 31,24 mg/kg, Natrium (Na) sebesar 21,45 mg/kg dan Magnesium (Mg) sebesar 17,5 mg/kg, sedangkan Sargassum sp memiliki kandungan Kalsium (Ca) sebesar 10,50 mg/kg, Kalium (K)  sebesar 26.35 mg/kg, Natrium (Na) sebesar 30.55 mg/kg dan Magnesium (Mg) sebesar 18,7 mg/kg. Kata kunci : Biostimulan, SSA, mineral makro, fitohormon.